THE IMPLEMENTATION ANALYSIS OF WORDWALL GAME BASED LEARNING ON LEARNING MOTIVATION IN CLASS X TKJ 1 STUDENTS SMKN 1 KENDIT - Yuliana, Dyan; Khoiriyah, Malika; Seituni, Siti (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2025)
In today's digital era, the development of information and communication technology has brought changes in various aspects of life, including education. Technology is not only a tool, but also an inseparable part of the learning process. The problem that occurs in class X TKJ 1 SMKN 1 Kendit is the low learning motivation of students caused by the monotonous and uninteresting learning process. This is seen from the lack of student participation in asking and answering questions. In addition, the monotonous model of questions also triggers boredom in students and does not provide variety and appeal to students. One media that can be used is a Wordwall-based game-based learning media designed to increase student engagement and learning motivation. The purpose of this study is to implement Wordwall - based game-based learning media in the learning process and determine its effectiveness in increasing the learning motivation of class X TKJ 1 SMKN 1 Kendit students. The approach used in this study is a qualitative approach with an interactive qualitative research type. In this study, the type of interactive qualitative research used is a case study, with a purposive sampling technique. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques used include data collection in the field, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that students are more motivated and interested in learning with this Wordwall media. The implementation of Wordwall-based game-based learning creates a fun learning atmosphere, and adds new insights and experiences, so that students' learning motivation increases. So, it can be concluded that the implementation of Wordwall -based game-based learning media is effective and appropriate to be implemented in the Basics of Computer Network Engineering and Telecommunications in class X TKJ 1 SMKN 1 Kendit.